Analisa Persepsi Pengaruh Perbedaan Gender pada Prestasi Belajar Bahasa Inggris Mahasiswa Semester 2 Program Studi Manajemen STIE Tribuana - Ali Agus (Jurnal Penelitian Multidisiplin Ilmu, 2022)
This analyses aimed to find out (1) Is any influences of gender between male and female students to the score of English Final Test of students in Semester 2 Management Department in STIE Tribuana (2) How far is the influences of gender to the English Final Test scores of students in semester 2 Management Department in STIE Tribuana by comparing the students’ English Final Test Scores. This analyses use descriptive quantitative analyses due to we calculate data. The analyse shows that there is influence of gender to the Final Test score of students in semester 2 In English Final Test Management Department STIE Tribuana. From the test, there id result that score of i Sig = 0.033 dan thitung = 2,191 menawhile ttabel = 1,67469. Sdince score of Sig < 0,05 dan thitung > ttabel so H0 is rejected means that there is influence of gender to the free variable X (Langauge Competence) to the bound variabel Y (Score of English Final Test )with the comparasionas follows maksimum score for male students is 78.00. Minimum 56.00 averages is 82.33. meanwhile English Score for female students maksimum 90,00, minimum 56.00 with averages 76.80. English Score for female students are higher than male students’